Good governance in land administration projects: project preparatio, project implementation, and capacity building - Wehrmann, B.
(En)
Ilus., 4 ref.
Keywords: GESTION; TIERRAS; ENTORNO SOCIOECONOMICO; POLITICA DE DESARROLLO; ITALIA; GESTION PUBLICA; REFORMA AGRARIA: COLONIZACION Y COOPERATIVAS